EPIDEMIOLOGICAL PROFILE OF CASES OF SEXUAL VIOLENCE IN ANÁPOLIS - GOIÁS - BRAZIL, IN THE YEARS 2017 TO 2020 - Paula Luiza de Sousa; Ana Luiza Espíndula Rocha; Gabriela Magalhães Bandeira Gomes; Karina Dayane Gonçalves Moreira; Renata Reis Silva; Marcela de Andrade Silvestre; Constanza Thaise Xavier Silva (Universidade Federal do Paraná, 2023)
Objective: to identify the epidemiological profile of victims who suffered sexual violence, in Anápolis - Goiás - Brazil, between the years 2017 to 2020. Methods: descriptive study of quantitative nature. Data from the notification form of sexual violence registered in the Department of Epidemiological Surveillance were used. Chi-square test was used with a significance level of 5% (p<0.05). Results: 850 cases were notified, with the peak in 2020, 82.1% were female, between the age group of two to 10 years (42.2%), brown (61.2%) and single (37.1%). The main conduct carried out after sexual violence was blood collection (21.6%); the main aggressors were the parents (20.9%), the main type of sexual violence was rape (68.7%) and the victims were mainly referred to the Guardianship Council (48.2%). Conclusion: The results point to the need to strengthen interventions to expand the social protection network for children and adolescents.